Refractory fallopian tube carcinoma – current perspectives in pathogenesis and management - Sama AR; Schilder RJ (Dove Medical Press, 2014)
Ashwin R Sama, Russell J SchilderDepartment of Medical Oncology, Thomas Jefferson University, Philadelphia, PA, USAAbstract: Fallopian tube carcinoma (FTC) is considered a rare malignancy, but recent evidence shows that its incidence may have been underestimated. Risk-reducing salpingo-oophorectomy (RRSO) in breast cancer susceptibility gene (BRCA)-positive women has provided a unique opportunity to study the pathogenesis of FTC and ovarian carcinomas. Newer data now suggest that most high-grade serous cancers of the ovary originate in the fimbrial end of the fallopian tube. Due to the presumed rarity of FTC, most current and more recent ovarian cancer clinical trials have now included patients with FTC. The treatment guidelines recommend similar overall management and that the same chemotherapy regimens be used for epithelial ovarian cancers and FTC.Keywords: high grade serous cancers, serous tubal intraepithelial carcinomas, fallopian tube carcinoma